A Prospective Controlled Study on Long-Term Outcomes of Facial Lacerations in Children - Fontana, Sonja; Schiestl, Clemens M.; Landolt, Markus A.; Staubli, Georg; von Salis, Sara; Neuhaus, Kathrin; Mohr, Christoph; Elrod, Julia (Frontiers in Pediatrics, 2021)
Background: Although skin adhesives have been used for decades to treat skin lacerations, uncertainty remains about long-term results, and complications. Methods: In this prospective, controlled, single-blinded, observational cohort study, outcomes were assessed by five plastic surgeons with standardized photographs at 6–12 months using a modified Patient and Observer Scar Assessment Scale (POSAS) and Vancouver Scar Scale (VSS); additionally, the POSAS was performed by the patients/caregivers and the physician; pain, requirement of anesthesia, treatment time, costs, complications, and quality of live (QoL) were assessed. Results: A total of 367 patients were enrolled; 230 were included in the main analysis; 96 wounds were closed using tissue adhesives (group 1); 134 were sutured (group 2). Assessment by the independent observers revealed an improved mean modified overall POSAS score in group 1 in comparison with group 2 [2.1, 95% CI [1.97–2.25] vs. 2.5, 95% CI [2.39–2.63]; p < 0.001, d = 0.58] and mean VSS score [1.2, 95% CI [0.981–1.34] vs. 1.6, 95% CI [1.49–1.79], p < 0.001, d = 0.53]. At the early follow-up, dehiscence rate was 12.5% in group 1 and 3.7% in group 2 (p < 0.001); later on, one dehiscence remained per group. Mild impairment of QoL was found at the early follow-up in both groups, with no impairment remaining later on. Duration of treatment and treatment costs were lower in group 1. Conclusion: Both modalities of wound closure yield favorable esthetic results, and complications are rare. Adhesives are more cost-effective, and its application is less time-consuming; therefore, tissue adhesives offer considerable advantages when used appropriately. Trial Registration: Public trial registration was performed at www.ClinicalTrials.gov (Identifier: NCT03080467).